Analysis of the Influence of Digital Transformation on the Financial Performance of Retail Companies in Indonesia - Nursafitri, Sintia; Juwita, Tia Permata; Irianto, Ellen D. Oktanti; Angriani Zn, Sefrimel (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Digital transformation has become a key factor in the evolution of the retail industry in Indonesia, especially with the increasing adoption of technology in various business operations. This study aims to analyze the impact of digital transformation on the financial performance of retail companies in Indonesia. Using a quantitative approach, this research examines secondary data from annual reports and financial statements of 16 retail companies listed on the Indonesia Stock Exchange (BEI) for the period 2021-2023. Digital transformation is measured based on the ratio of digital intangible assets to total intangible assets, while financial performance is measured using Return on Assets (ROA). The results of a simple regression analysis indicate that digitaltransformation has a significant negative impact on ROA, with each increase in digital transformation associated with a decrease in ROA by 1.381. These findings suggest that poorly managed digital transformation implementation can hinder acompany's financial performance. According to the Resource-Based View (RBV) theory, companies with sufficient resources and capabilities can optimize the benefits of digital transformation, while those with limited resources may experience a decline in financial performance. This study provides insights for industry players on the importance of an effective digital strategy in enhancing competitiveness and operational efficiency. Therefore, retail companies need to conduct thorough planning, strengthen internal capabilities, and regularly evaluate the implementation of digital transformation to minimize its negative impact on profitability.